Theater of the world : the maps that made history - Reinertsen Berg, Thomas, 1971- (Little, Brown and Company, 2018)
Theater of the World offers a fascinating history of mapmaking, using the visual representation of the world through time to tell a new story about world history and the men who made it. Thomas Reinertsen Berg takes us all the way from the mysterious symbols of the Stone Age to Google Earth, exploring how the ability to envision what the world looked like developed hand in hand with worldwide exploration. Along the way, we meet visionary geographers and heroic explorers along with other unknown heroes of the map-making world, both ancient and modern. And the stunning visual material allows us to witness the extraordinary breadth of this history with our own eye.